A preliminary investigation of incorporating cellulose nanocrystals into engineered cementitious composites - Yang, Xiao; Ren, Jian-Guo; Li, Lian-Xu; Wang, Zhen; Zhang, Qi-Hang; Liu, Qiao-Ling (Frontiers in Materials, 2024)
This paper explored the effects of various amounts of cellulose nanocrystals (CNCs), namely 0%, 0.1%, 0.2%, and 0.4% of binder weight, on the rheology, pore structure, mechanical properties, and 3D distribution of fibers of an engineered cementitious composite (ECC). The two rheological parameters, namely the yield stress and plastic viscosity, of the matrix containing the CNCs increased. Low-field nuclear magnetic resonance (LF-NMR) analysis, as a non-destructive method, proved that the addition of the CNCs to the ECC could reduce the porosity of the material and refine its pore size distribution. The addition of the CNCs enhanced the compressive strength of the ECC by 19.6–33%. The results from uniaxial tensile tests showed incorporating the CNCs into the matrix could enhance the initial cracking strength and ultimate tensile strength of the ECC but reduce their tensile strain-hardening capacity. The optimal addition of 0.1% CNCs could effectively offset the decrease in strength due to increasing FA content, and maintain a relatively high level of tensile strain capacity of over 3%. Finally, X-ray micro-computed tomography (micro-CT) with ORS Dragonfly software was employed to reconstruct 3D images of the ECC to present the improvement in the fiber distribution due to the addition of the CNCs.